2021
DOI: 10.19245/25.05.pij.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding Towards the Future: The Need of Different Research Perspectives

Abstract: In serving as editor of this special issue of PIJ on crowdfunding, I want to pursue two main goals. Obviously, on the one hand, it is necessary to underline the relevance of each of the accepted papers hereafter published, thus presenting -from my point of view -the most fascinating contributes to the academic debate about this kind of financing channel. On the other, I think that it is even more useful for future research development to try to depict a possibly more open research agenda on this very wide phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…Social media is also a place that is widely used in text analysis and SNA research. Therefore, this study supports Previati's (2021) research, which suggests the need for new approaches in crowdfunding research, one of which is the SNA approach.…”
Section: Hariwibowosupporting
confidence: 78%
See 2 more Smart Citations
“…Social media is also a place that is widely used in text analysis and SNA research. Therefore, this study supports Previati's (2021) research, which suggests the need for new approaches in crowdfunding research, one of which is the SNA approach.…”
Section: Hariwibowosupporting
confidence: 78%
“…The results of this study demonstrated that, although it is not the main thing that young people pay attention to, some types of crowdfunding projects can attract young people to contribute. If these results are attributed to other factors in the same modularity, projects that appeal to young people can provide project confidence through the narratives built into those platforms (H. Zhou & Ye, 2019, 2021M. Zhou et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation